Characterization and modeling of the serum concentration of osteocalcin in breeding sows and its interaction with biochemical indicators: A review - Ordaz, Gerardo; Rentería, José Antonio; Mariscal, Gerardo (Journal of Advanced Veterinary and Animal Research, 2022)
Adipose, muscle, and bone tissues modulate the metabolic state of mammals. However, the role of bone tissue as a metabolic state modulator in sows has not been studied. During the gestation– lactation transition, sows undergo metabolic adaptations to meet their nutritional requirements. Among these adaptations, bone remodeling is characterized by the synthesis and inhibition of hormones that participate, together with hormones from other tissues, in fetal development and lactogenesis. Osteocalcin is a hormone synthesized by the bone tissue which has been associated in different biological models with the improvement of the metabolic state. However, in sows, published results on the concentration of osteocalcin are scarce, and its concentration throughout the reproductive cycle is unknown. Therefore, with information from published trials on the measurement of serum osteocalcin, a structured review was conducted under the following objectives: (1) to review the promising effect of osteocalcin on energy metabolism in different models and (2) to characterize and model the serum concentrations of osteocalcin during the reproductive cycle of the sow. According to the review, the results obtained for humans and other animal models suggest that osteocalcin regulates energy metabolism, which has been associated with the need for integrated metabolism to cope with the metabolic demand during gestation and lactation in mammals. If these effects are significant in the sow, current recommendations for dietary balance should be reconsidered, particularly during the gestation–lactation transition period. According to mathematical modeling, it was the period in which the lowest concentration of osteocalcin was found. J. Adv. Vet. Anim. Res., 9(4): 634–648, December 2022 http://doi.org/10.5455/javar.2022.i633